2014
DOI: 10.3168/jds.2013-7709
|View full text |Cite
|
Sign up to set email alerts
|

Rumination time around calving: An early signal to detect cows at greater risk of disease

Abstract: The main objective of this experiment was to evaluate the use of rumination time (RT) during the peripartum period as a tool for early disease detection. The study was carried out in an experimental freestall barn and involved 23 Italian Friesian cows (9 primiparous and 14 multiparous). The RT was continuously recorded by using an automatic system (Hr-Tag, SCR Engineers Ltd., Netanya, Israel), and data were summarized in 2-h intervals. Blood samples were collected from 30 d before calving to 42 d in milk (DIM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
99
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 43 publications
13
99
2
3
Order By: Relevance
“…For example, changes in the rumination patterns and daily amount of time spent ruminating were associated with metabolic disorders and were detected several hours or days before onset of clinical symptoms (Fitzpatrick et al, 2013;Calamari et al, 2014). In sheep, ewes diagnosed with subclinical mastitis increased vocalization and reduced head-up postures compared with healthy ewes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in the rumination patterns and daily amount of time spent ruminating were associated with metabolic disorders and were detected several hours or days before onset of clinical symptoms (Fitzpatrick et al, 2013;Calamari et al, 2014). In sheep, ewes diagnosed with subclinical mastitis increased vocalization and reduced head-up postures compared with healthy ewes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the fact that dietary changes and nutritional shifts can increase the chance of ruminal/metabolic diseases, and may cause more drastic modifications to the future evolutionary adaptations of ruminant digestive system [9,12], new approaches of evaluating ruminal behavior may be a strong marker to predict the risk of diseases and suitable herd welfare [13][14][15][16]. Hence, this review aims to provide recent information of the associations between ruminal behavior and metabolic disorders.…”
Section: The Role Of Ruminants On Global Food Systemmentioning
confidence: 99%
“…After the indications that rumination behavior may be a promising indicator of metabolic conditions, new methods to measure and evaluate herd performance have typically focused on feeding comportment in ruminants [30]. Therefore, the introduction of a novel method to indirectly measure RT, evaluates vocal signs and allows automatic measurement of RT to analyze rumination behavior in different environments [13,22]. Results of these studies found that cows with different health problems ruminate less then healthy cows, and therefore, there is a relationship between RT and metabolic conditions such as ketosis, hypocalcemia, and inflammatory blood markers around calving [13,14,22,30].…”
Section: Measurements Of Cow Behavior Identify Animals At Risk For Ilmentioning
confidence: 99%
See 2 more Smart Citations